Innovative Teaching Aids for French Language: A Study of Teachers' Perspectives and Challenges in Nigerian Schools (British Journal of Multidisciplinary and Advanced Studies, 2026)
This study assesses innovative teaching aids for French Language: A study of teachers’ perspective and challenges in Nigerian schools. This study employed a descriptive research design of the survey type to systematically collect and analyze data on French teachers' perceptions of innovative teaching aids. The population comprised 1,001 French Language teachers across selected schools in Southwest Nigeria, with a sample size of 115 determined through stratified random sampling to ensure representativeness. Data were collected using a structured questionnaire titled French Teachers' Perception on Innovative Teaching Aids (FTPITA), which was validated through expert review in French Language education. The reliability of the instrument was confirmed with a coefficient of 0.91, indicating high internal consistency. The questionnaire was administered electronically, ensuring a high response rate. Data analysis involved descriptive statistics (percentages, mean, and standard deviation) to summarize demographic characteristics and overall perceptions, while inferential statistics (t-test and regression analysis) were used to examine relationships and differences between variables. Hypotheses were tested at a 0.05 level of significance, ensuring statistical rigor in determining meaningful patterns. The findings of the study reveal that teachers acknowledge the benefits of innovative teaching aids in improving student engagement and learning in French instruction. However, their effective use is hindered by inadequate training, limited access to resources, poor infrastructure, and insufficient government support. While teachers do not see traditional methods as superior, schools face shortages of multimedia tools, language labs, and internet access. Funding constraints, lack of external collaborations, and insufficient professional development further restrict integration. Despite confidence in using technology, structured training remains inadequate, making financial and institutional barriers key challenges to adopting modern teaching aids. It was recommended among others that the government and school administrators should allocate more funding for procuring innovative teaching aids such as multimedia tools, language laboratories, and stable internet connectivity to improve instructional delivery.